Intercultural Communication Competence for Public School Teachers: A Phenomenological Study - Panji Hendrarso; Baby Poernomo; Nicole Chai; Carmelita Carmelita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the successes of education lies in the quality of good teachers. One of them is competence in the field of intercultural communication, especially because Indonesia a saais very multicultural so it cannot be avoided that in every class student from different backgrounds such as culture, religion, race, socio-economic conditions, and also students with special needs are encountered. However, until now, there are still many teachers, especially in public schools, who are considered not to have intercultural communication competence. However, until now, there are still many teachers, especially in public schools, who are considered not to have intercultural communication competence, causing students with different cultural backgrounds to feel uncomfortable studying in public schools. This study aims to answer the question of how the intercultural communication competence of teachers in public schools and what obstacles are encountered by students who have different cultural backgrounds in pursuing their education in public schools, and what efforts should be made so that teachers in public schools can improve their competence in intercultural communication. This is qualitative research with a phenomenological approach because this study wants to dig deeper into the experiences experienced by parents and public elementary school students with special needs and students of different ethnicities and religions. Data collection in this study used semi-structured interviews semi structured interview with 21 informants consisting of students, parents and education practitioners. The results of this study indicate that the intercultural communication competence of teachers in public schools still needs improvement.